Anti-inflammatory and anti-tumor-promoting effects of 5-deprenyllupulonol C and other compounds from hop (Humulus lupulus L.) - Akazawa H. (2014)
A new phloroglucinol derivative, 5-deprenyllupulonol C (1), along with four other phloroglucinol derivatives, 2-5, five chalcones, 6-10, four flavanones, 11-14, two flavonol glycosides, 15 and 16, and five triterpenoids, 17-21, were isolated from the female inflorescence pellet extracts of hop (Humulus lupulus L.). Upon evaluation of these compounds against the Epstein-Barr virus early antigen (EBV-EA) activation induced by 12-O-tetradecanoylphorbol 13-acetate (TPA) in Raji cells, twelve compounds, i.e., 1-4, 11-14, 17-19, and 21, showed potent inhibitory effects on EBV-EA induction, with IC 50 values in the range of 215-393 mol ratio/32 pmol TPA. In addition, eleven compounds, i.e., 1-4, 6, 11, 12, 14, 17, 18, and 20, were found to inhibit TPA-induced inflammation (1 μg/ear) in mice, with ID 50 values in the range of 0.13-1.06 mmol per ear. Further, lupulone C (2) and 6-prenylnaringenin (14) exhibited inhibitory effects on skin-tumor promotion in an in vivo two-stage mouse-skin carcinogenesis test based on 7,12-dimethylbenz[a]anthracene (DMBA) as initiator and with TPA as promoter. © 2012 Verlag Helvetica Chimica Acta AG.